2022
DOI: 10.1037/cou0000632
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception matters: Reciprocal relations between adolescents’ depressive symptoms and parental perceptions.

Abstract: A large body of research has shown that parents play a vital role in the development of adolescents' depression. However, previous research has overlooked the effects of a potentially critical factor, namely, parental perceptions, and beliefs about adolescents' depression. The present study examined whether parental perceptions of an adolescent's depressive symptoms predict longitudinal changes in adolescents' symptoms (i.e., the parental perception effect). The longitudinal relationship between adolescents' d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 75 publications
2
8
0
1
Order By: Relevance
“…Similar to what Ohtani et al (2022) found, this pattern of findings could refer to a Pygmalion effect (Rosenthal & Jacobson, 1968) where adolescents were influenced by their parent's perceptions of their own need satisfaction. While studies investigating both parental perceptions and children or adolescent perceptions are rare, similar effects appear in the literature on adults' expectations of children and adolescents.…”
Section: The Parental Perception Effectsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar to what Ohtani et al (2022) found, this pattern of findings could refer to a Pygmalion effect (Rosenthal & Jacobson, 1968) where adolescents were influenced by their parent's perceptions of their own need satisfaction. While studies investigating both parental perceptions and children or adolescent perceptions are rare, similar effects appear in the literature on adults' expectations of children and adolescents.…”
Section: The Parental Perception Effectsupporting
confidence: 82%
“…Assessing parents' perceptions of adolescents could provide important information to guide interventions and explain the maintenance of certain perceptions of autonomy, competence, and relatedness that underpin various negative emotional and behavioral outcomes in adolescents (Rodrı´guez-Meirinhos et al, 2021). Finally, as Ohtani et al (2022) suggested, parents could also be made aware of their influential power and use it to positively support their children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of work has explored the role of parents’ conditions and practices in their children’s mental healht and related service use. 16,17 Research on the specific contribution of parents’ stigmatising attitudes has been relatively small and focussed on children’s help-seeking practices. 18 One U.S. study found that boys aged 13-14 were less willing to seek mental health services if their parents disapproved of such services compared with girls.…”
Section: Introductionmentioning
confidence: 99%